2022
DOI: 10.1002/osp4.649
|View full text |Cite
|
Sign up to set email alerts
|

The healthful plant‐based diet index as a tool for obesity prevention—The healthy lifestyle community program cohort 3 study

Abstract: Background: World-wide the prevalence of obesity is high, and promoting a shift toward more healthful and more plant-based dietary patterns appears to be one promising strategy to address this issue. A dietary score to assess adherence to a healthy plant-based diet is the healthful plant-based diet index. While there is evidence from cohort studies that an increased healthful plant-based diet index is associated with improved risk markers, evidence from intervention studies is still lacking. Methods:A lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…Published data from the Healthy Lifestyle Community Program (HLCP-1,HLCP-2 and HLCP-3), an intensive lifestyle intervention with a community-based approach, have shown that the program can result in metabolic and anthropometric improvements [14][15][16][17]. For body weight, the primary outcome parameter, we had hypothesized that the lifestyle intervention would lead to a significant reduction within the intervention group (IG) compared to the control group (CG) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Published data from the Healthy Lifestyle Community Program (HLCP-1,HLCP-2 and HLCP-3), an intensive lifestyle intervention with a community-based approach, have shown that the program can result in metabolic and anthropometric improvements [14][15][16][17]. For body weight, the primary outcome parameter, we had hypothesized that the lifestyle intervention would lead to a significant reduction within the intervention group (IG) compared to the control group (CG) [17].…”
Section: Introductionmentioning
confidence: 99%